Teacher-centered or Student-centered Learning Approach to Promote Learning? - Ive Emaliana, (Jurnal Sosial Humaniora, 2025)
This study investigates English department students learning needs including their attitudes towards student-centered and traditional teaching approaches, culture learning in English as Foreign Language (EFL) program, attitudes towards authority in class, the main problems encountered in the course in learning English and their practice of language learning strategies. In this empirical study, following Xiao’s (2006) questionnaire, the data are collected from undergraduates and postgraduates students. In analyzing the groups, one-way ANOVA Test is used to identify whether the mean score on a variable differed significantly from one group to another by taking into account variation within groups as well as between groups. The findings of this research provide EFL teachers with insightful information on students’ learning needs as an input to syllabus and material planning, to lesson planning and classroom instruction practice. The study demonstrates the importance of a good understanding of students’ variables in TEFL programs at university level in Indonesia.